Reimbursement decision-making system in Poland systematically compared to other countries - Mela, Aneta; Rdzanek, Elżbieta; Jaroszyński, Janusz; Furtak-Niczyporuk, Marzena; Jabłoński, Mirosław; Niewada, Maciej (Frontiers in Pharmacology, 2023)
Our objective was to analyze and compare systematically and structurally reimbursement systems in Poland and other countries. The systems were selected based on recommendations issued by the Polish Agency for Health Technology Assessment and Tariffication (AHTAPol), which explicitly referred to other countries and agencies). Consequently, apart from Poland, the countries included in the analysis were England, Scotland, Wales, Ireland, France, the Netherlands, Germany, Norway, Sweden, Canada, Australia and New Zealand. Relevant information and data were collected through a systematic search of PubMed (Medline), Embase and The Cochrane Library as well as competent authority websites and grey literature sources. In most of the countries, the submission of a reimbursement application is initiated by a pharmaceutical company, and only a few countries allow it before a product is approved for marketing. All of the agencies analyzed are independent and some have regulatory function of reimbursement decision making body. A key criterion differentiating the various agencies in terms of HTA is the cost-effectiveness threshold. Most of the countries have specific mechanisms to improve access to expensive specialty drugs, including cancer drugs and those used for rare diseases. Reimbursement systems often lack consistency in appreciating the same stages, leading to heterogeneous decision-making processes. The analysis of recommendations issued in different countries for the same medicinal product will allow a better understanding of the relations between the reimbursement system, HTA assessment, stakeholders involvement and decision on reimbursement of innovative drugs.